Simulasi Pengaruh Variasi Beban Produk pada Tegangan, Displacement dan Factor of Safety pada Bearing Sabuk Konveyor - Abdul Mu'is Sulaiman; Hisyam Ma’mun; Muhammad Budi Haryono (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2026)
Continuous production processes can lead to sudden bearing failure in conveyor belts, potentially stopping operations. This study aims to analyze stress, displacement, and the factor of safety (FOS) of a bearing using the Finite Element Analysis (FEA) method. Static simulations were conducted using SolidWorks to model the bearing under conveyor operating conditions. The applied loads were 94.49 N, 94.76 N, and 95.04 N, with a conveyor speed of 3 m/s. The results show that the maximum von Mises stress ranges from 17.36 MPa to 17.39 MPa, which is far below the yield strength of chrome steel AISI 52100 at 2033.95 MPa. The maximum displacement is very small, at 0.0004798 mm, remaining within safe limits. The average FOS is 12.7, significantly exceeding the minimum standard of 1.25 according to Mott’s theory, indicating high structural reliability despite signs of overdesign. It can be concluded that the SKF 6003 bearing is safe for use under these operating conditions.